Formulation and Evaluation of Novel Antibacterial Tooth Powder - Samathoti, Prasanthi (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: The current novel research work aims in preparing various formulations of antibacterial tooth powder and evaluates for the best formulation among the fabricated formulations. Materials and Methods: The antibacterial agents chosen were thymol and camphor, bentonite for detoxification, calcium carbonate for abrasion, peppermint oil for flavoring, sodium saccharin for sweetness, and sodium lauryl sulfate for foaming. A total of six formulations were done by naming F1 to F6 with various combinations of all the agents. Carr’s index, angle of repose, moisture content determination, foaming power determination, physical appearance/ visual inspection, pH determination, bulk density and tapped density determination, and in vitro antibacterial activity against Staphylococcus aureus by agar well-diffusion method were all used to assess each formulation. Results and Discussion: Based on a comprehensive analysis of all formulation evaluations, F3 is deemed the best due to its superior antibacterial activity, foaming power, and all other evaluations. A 24-h incubation period confirms the antibacterial activity. Conclusion: F3 might yield extremely positive and encouraging outcomes in achieving the current work’s goal.